Fecal microbiota transplantation modulates jejunal host-microbiota interface in weanling piglets - Shankumar Mooyottu; Muhammed Shafeekh Muyyarikkandy; Farnaz Yousefi; Ganwu Li; Orhan Sahin; Eric Burrough; Joy Scaria; Brett Sponseller; Alejandro Ramirez (Microbiome)
Abstract Background Weaning-associated enteric diseases are a major concern in the swine industry. This study investigates the effects of fecal microbiota transplantation (FMT) on the jejunum of weanling piglets, a segment of bowel less studied in terms of microbiomic changes despite its primary involvement in major post-weaning enteric diseases, including postweaning diarrhea (PWD). Thirty-two 3-week-old piglets were divided equally into two groups: Control and FMT. The FMT group received fecal microbiota preparation from 3-month-old healthy pigs on the 1st and 3rd day after weaning. Half of each group was inoculated with an enterotoxigenic E. coli (ETEC) isolate 10 days post-FMT. Piglets were euthanized in the third week (14th and 18th days post-FMT) after weaning to collect intestinal tissues and contents for microbiomic, metabolomic, and transcriptomic analyses. Results The jejunal microbiota showed a significant increase in alpha diversity in the third week post-FMT compared with the ileum and colon. FMT significantly enriched the jejunal microbiota composition, while multiple bacterial genera were specifically lacking in control weanling piglets. FMT was strongly associated with the enrichment of the genus Pseudoscardovia of the Bifidobacteriaceae family, which was found lacking in the jejunum of weanling control piglets and inversely associated with the abundance of the genus Bifidobacterium within the same family. Other genera associated with FMT included Solobacterium, Shuttleworthia, and Pseudoraminibacter, whereas bacteria such as Erysipelotrichaceae and Acidaminococcus were identified as most abundant in the control piglets. Metabolomic analysis revealed a significant modulatory effect of FMT on carbohydrate, amino acid, nucleotide, vitamin, and xenobiotic metabolisms, suggesting improved nutrient utilization. Transcriptomic analyses further confirmed the regulatory effects of FMT on gene expression associated with immune, metabolic, barrier, and neuroendocrine functions. Prior FMT treatment in the context of ETEC infection indicated a potential protective role, as evidenced by a significant shift in microbial diversity and metabolomic compositions and decreased diarrhea severity even though no effect on pathogen shedding was evident. Conclusions This study underscores the promise of FMT in enhancing jejunal health. In addition, the results suggest that FMT could be considered a potential strategy to address conditions associated with small intestinal dysbiosis in swine and other monogastric species with similar gut anatomy and physiology, such as humans. Video Abstract